2015
DOI: 10.3389/fnana.2015.00131
|View full text |Cite
|
Sign up to set email alerts
|

The maturation of auditory responses in infants and young children: a cross-sectional study from 6 to 59 months

Abstract: Background: An understanding of the maturation of auditory cortex responses in typically developing infants and toddlers is needed to later identify auditory processing abnormalities in infants at risk for neurodevelopmental disorders. The availability of infant and young child magnetoencephalography (MEG) systems may now provide near optimal assessment of left and right hemisphere auditory neuromagnetic responses in young populations. To assess the performance of a novel whole-head infant MEG system, a cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
(88 reference statements)
2
22
0
Order By: Relevance
“…Another limitation is that we only measured the structure of the pathways, and not auditory function. Other studies have focused on the association between white matter maturation in the auditory cortex and single‐cell electrophysiology in animal models, or used other techniques (i.e., Magnetoencephalography, Electroencephalography) to examine the development of human auditory cortex function during both typical and atypical development (Edgar et al, ; Kikuchi, Yoshimura, & Minabe, ; Roberts et al, ; Roberts, Lanza, Dell, Qasmieh, & Hines, ). Future multimodal studies, therefore, are needed in order to follow the specific development of these pathways and relate them with the development of auditory processing abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we only measured the structure of the pathways, and not auditory function. Other studies have focused on the association between white matter maturation in the auditory cortex and single‐cell electrophysiology in animal models, or used other techniques (i.e., Magnetoencephalography, Electroencephalography) to examine the development of human auditory cortex function during both typical and atypical development (Edgar et al, ; Kikuchi, Yoshimura, & Minabe, ; Roberts et al, ; Roberts, Lanza, Dell, Qasmieh, & Hines, ). Future multimodal studies, therefore, are needed in order to follow the specific development of these pathways and relate them with the development of auditory processing abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies examining auditory processes in infants and children also are of interest given that treatments seeking to normalize auditory processes in ASD will likely target younger rather than older populations in order to have a better chance at normalizing auditory processes. In these studies, use of a whole-head infant MEG system is preferred given that MEG sensors are closer to the head in infant versus adult MEG systems [ 59 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a repeated session would have provided a powerful control for natural variability over time in WM responses. We did not collect a second MEG session in controls because of the cost of MEG, and because there are many publications that have shown high test–retest reliability for MEG metrics (Ahonen, Huotilainen, & Brattico, 2016; Becker et al, 2012; Edgar et al, 2015; Martín-Buro, Garcés, & Maestú, 2016; Tan, Gross, & Uhlhaas, 2015). Importantly, Ahonen and colleagues (2016) found that neurophysiological responses during an N -back WM task were highly reliable.…”
Section: Discussionmentioning
confidence: 99%